2005
DOI: 10.1183/09031936.05.00085304
|View full text |Cite
|
Sign up to set email alerts
|

A chart of failure risk for noninvasive ventilation in patients with COPD exacerbation

Abstract: on behalf of the Italian noninvasive positive pressure ventilation (NPPV) study group ## ABSTRACT: Knowing the likelihood of failure of noninvasive positive pressure ventilation (NPPV) in patients with exacerbation of chronic obstructive pulmonary disease (COPD) could indicate the best choice between NPPV and endotracheal intubation instituted earlier. For this purpose, two risk charts were designed (at admission and after 2 h of NPPV) that included all relevant measurable clinical prognostic indicators derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
265
7
21

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 327 publications
(324 citation statements)
references
References 33 publications
31
265
7
21
Order By: Relevance
“…During this period, each participating hospital completed a pre-defined dataset about the resources and the organisation of acute COPD care listed in online supplementary table s1. For the risk prediction models, respiratory acidosis was stratified as severe with a pH <7.25 and mild with a pH 7.25-7.35 [10,11]. The staff resources, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…During this period, each participating hospital completed a pre-defined dataset about the resources and the organisation of acute COPD care listed in online supplementary table s1. For the risk prediction models, respiratory acidosis was stratified as severe with a pH <7.25 and mild with a pH 7.25-7.35 [10,11]. The staff resources, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…4,25 Moreover, noninvasive physiological data at baseline and after 2 hours of NIV can accurately predict the likelihood of NIV failure in COPD exacerbation. 26 Almost all the RHDCUs had NIV ventilators, which, in contrast to older-generation ICU ventilators, can adequately compensate for air leaks. 27 …”
Section: Levels Of Care Locations and Resourcesmentioning
confidence: 99%
“…Passarini et al (15) observing patients with COPD and APE, found that higher scores on the GCS were predictive of success of NIV. Similarly, Confalonieri et al (16) found that patients with GCS below 11, pH ≥ 7.25, respiratory rate ≥ 30 breaths per minute, and high level predictive of mortality on admission had risk > 70% of failure of NIV.…”
Section: Discussionmentioning
confidence: 99%